2004
DOI: 10.1016/j.febslet.2004.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cγ2 contributes to stable thrombus formation on VWF

Abstract: Though phospholipase C PLCc2 is known to play an important role in platelet activation by collagen and fibrinogen, its importance in GPIb-mediated platelet activation is less well understood. To better understand the role of PLCc2 in GPIbmediated adhesion and thrombus formation, we examined the ability of wild-type and PLCc2-deficient murine platelets to spread on immobilized von Willebrand factor (VWF) under static conditions, and to attach to and form thrombi on VWF under conditions of arterial shear. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…However, the PLC-selective basis of these pharmacological inhibitors is unclear. Published data showing that Plcg2 -/-platelets have a spreading defect following adhesion to collagen, fibrinogen or vonWillebrand factor (Asselin et al, 1997;Goncalves et al, 2003;Inoue et al, 2003;Wonerow et al, 2003;Rathore et al, 2004) concurs with our data. In contrast to our data, Plcg2 -/-platelets do not show deficits in cell adhesion.…”
Section: Discussionsupporting
confidence: 81%
“…However, the PLC-selective basis of these pharmacological inhibitors is unclear. Published data showing that Plcg2 -/-platelets have a spreading defect following adhesion to collagen, fibrinogen or vonWillebrand factor (Asselin et al, 1997;Goncalves et al, 2003;Inoue et al, 2003;Wonerow et al, 2003;Rathore et al, 2004) concurs with our data. In contrast to our data, Plcg2 -/-platelets do not show deficits in cell adhesion.…”
Section: Discussionsupporting
confidence: 81%
“…The tyrosine kinase Syk and the effector enzyme PLC␥2 play critical roles in platelet spreading downstream of integrins ␣ IIb ␤ 3 and ␣ 2 ␤ 1 . [5][6][7]20,21 As shown in Figure 2, analysis by DIC microscopy revealed that formation of lamellipodia in mouse platelets on laminin was almost completely inhibited in the absence of Syk or PLC␥2, although there was no effect on the level of adhesion. Interestingly, the degree of inhibition of spreading was more marked in the absence of Syk relative to the absence of PLC␥2.…”
Section: Dissection Of Signaling Events In Platelet Spreading On Lamininmentioning
confidence: 99%
“…Thus, collagen binding to the integrin ␣2␤1 uses both the ITAM-bearing GPVI/FcR␥ chain [59][60][61] as well as PLC␥2 17 to transmit activation signals, as does the integrin ␣6␤1 when platelets encounter the extracellular matrix protein laminin. 62,63 Similarly, interaction of von Willebrand factor with the platelet GPIb complex results in activation of Src family kinases, Syk, and PLC␥2, 64-67 and we and others have shown a critical role for PLC␥2 in supporting platelet spreading 66,68 and thrombus formation 68 on immobilized VWF under conditions of flow. Unlike collagen, laminin, or fibrinogen binding-induced activation, however, VWF-induced platelet activation does not appear to require Fc␥RIIa or the FcR␥ chain to transmit adhesiondependent signals, 66,69 although their ability to serve as costimulatory signal amplification molecules, when present, has not been ruled out.…”
Section: Outside-inmentioning
confidence: 99%